(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
In recent years, the number of international students in Uzbekistan, particularly from India, has increased exponentially. This is due to the expansion of cultural and business ties between the countries, the high quality of higher medical education in Uzbekistan, and relatively low tuition fees. Students from India face unique linguistic and cultural characteristics, a historical context, and differences in educational and everyday traditions in Uzbekistan, which may lead to difficulties adapting to a new country and intercultural communication.